Participation in India : An Analysis of NSS 64th Round Data - Sankar, Deepa (World Bank, Washington, DC, 2017)
The significance of secondary education emerges from its critical role in promoting economic growth by determining the quality of those who enter labor market after schooling as well as those who pursue higher education. Secondary education is also important due to the positive externalities on promoting health, social cohesion and sustainable livelihood. Secondary education is undeniably the crucial stage in any education system, as it is in this stage that the elementary school graduates get their basic skills cemented and gain competencies that prepare them to enter either into higher education or into labor market. This analytical report presents the status of secondary education participation the participation in India using National Sample Survey (NSS) 64th round (2007-08). The specific objectives of this policy note are: a) the participation rates of adolescents in secondary education, disaggregated by gender, social and religious groups, household economic quintiles and different locations (rural or urban as well as across states) in India using NSS 64th round (2007-08); b) the transition patterns from elementary to secondary stage and dropouts in between, disaggregated; and c) the proportion of population who had secondary education; and participation in secondary education by type of management of schools. This policy note is organized in the following way. In the first section, a brief account of the secondary education scenario in the country is provided. In the second section, overall secondary education participation is analyzed. In section three, an analysis of gender and social or religious gaps in secondary education participation is taken up.